Equalization Schemes in German Unemployment Compensation - Rohrlich, George F. (Quarterly Journal of Economics, 1944)
Relevance of the German experience, 482. — I. Coöperation for the relief of the unemployed, 1918–1927: early demobilization measures, 483; unemployment relief measures, 484; nation-wide equalization, 486. — II. The national unemployment insurance act of 1927: federal and state contributions, 488; effects of the depression, 490. — III. Extent of financial equalization, 1924–1936: national and state contributions to the cost of unemployment relief, 490; equalization within the Federal Institute, 493. — IV. Conclusions, 496.